SOSIALISASI PEMBUATAN JAMU KEKINIAN DAN JAMU INSTAN DI DUSUN KADIBESO, ARGODADI, SEDAYU, BANTUL, DIY - Fatmawati, Annisa (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2021)
The people in Kadibeso Hamlet, Argodadi Village, Sedayu, Bantul, have never received socialization and training on making instant herbal medicine. The methods used in conducting the socialization and workshop on making instant herbal medicine to the people of Dusun Kadibeso: counseling on "Utilizing TOGA" and a demonstration on how to make a "contemporary" drink from turmeric juice (Curcuma longa Linn) mixed with milk, as well as making instant ginger (Zingiber officinale). The results of interviews and distribution of questionnaires after the socialization and workshop on making herbal medicine “Curmilk”, all participants understood the material given with a 100% understanding percentage. Traditional herbal medicine in liquid form has the disadvantage that it is not durable, because it is easily overgrown by bacteria and fungi. So, the innovation of making instant ginger powder “provides a solution”, so that herbal preparations can be stored longer and can become a commodity for traditional medicinal products. Jamu which is packaged in the form of today's products is an opportunity to elevate traditional Indonesian medicines into superior products that are beneficial to health.